2020
DOI: 10.2147/copd.s225765
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circulating Biomarkers of Handgrip Strength and Lung Function in Chronic Obstructive Pulmonary Disease</p>

Abstract: Purpose: COPD is a multisystem disease and there is a need for clinical serum markers that can assess the decline in lung and muscle function in COPD. The goal of this study was to evaluate the potential association of serum club-cell protein 16 (CC16), α-1 acid glycoprotein (AGP) and total sialic acid (TSA) with spirometry, hand-grip strength and quality of life to assess important disease outcomes. Methods: This is a population-based cross-sectional study and data were collected from the patients at teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Several studies have investigated candidate biomarkers of lung and muscle health in COPD as a tool to monitor disease severity in COPD, which can be helpful in diagnosing and predicting the disease progress and response to therapy [ 7 , 27 , 28 , 29 ]. Our results demonstrated the clinical utility of plasma CAF22, which we proposed as a feasible, noncomplex marker of the muscle decline at various stages of COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have investigated candidate biomarkers of lung and muscle health in COPD as a tool to monitor disease severity in COPD, which can be helpful in diagnosing and predicting the disease progress and response to therapy [ 7 , 27 , 28 , 29 ]. Our results demonstrated the clinical utility of plasma CAF22, which we proposed as a feasible, noncomplex marker of the muscle decline at various stages of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Hand-grip strength was measured by a digital handgrip dynamometer (CAMRY, South El Monte, CA, USA) as described before [ 7 ]. The participants were instructed to sit down with their elbows flexed at an angle of 90° with the dynamometer in hand in the supine position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand-grip strength was measured using a digital handgrip dynamometer (CAMRY, South El Monte, CA, USA) as described before [ 26 ]. The participants were instructed to sit down with their elbows flexed at an angle of 90◦ with the dynamometer in hand in the supine position.…”
Section: Methodsmentioning
confidence: 99%
“…Various muscle diseases including genetic & inflammatory myopathies, cancer cachexia and sarcopenia result in prolonged elevation of SR stress and its downstream effects (12). Furthermore, a direct causality between SR stress and muscle detriment has also been proposed since mitigating SR stress can partially restore muscle mass and/or strength in experimental animal models (13,14).We have previously shown that the muscle weakness in COPD is associated with reduction in serum sialic acid (15), a monosaccharide with various biological functions. Sialic acid has involvement in SR stress and apoptosis (16) while deficiency of it leads to oxidative stress and atrophy in skeletal muscle (17).…”
Section: Introductionmentioning
confidence: 99%